CONSUMER INTEREST IN THE PROBOLAJANG PIPELINED DRINKING WATER SUPPLY SYSTEM - Santoso, Irwan Bagyo; muzayanah (Universitas Negeri Surabaya, 2023)
Procurement of regional piped drinking water supply system for Probolinggo and Lumajang Regency (Probolajang) is an effort by Government to improve drinking water supply system services. This research aims to analyze the public's interest in becoming consumers of the Probolajang piped drinking water supply system. The research area consist of 6 districts in Probolinggo Regency, 3 districts in Lumajang Regency and 3 districts in Probolinggo City. Respondents are families who are not subsribing to existing water system. The dependent variable is the respondent's interest in subscribing to the drinking water supply system. The independent variables are education, income, quality, quantity and continuity of raw water. Analysis method that used for this study is polynomial logistic regression. The result proves that the variables of education level, income and quantity of raw water have positive relationship with respondents' interest in becoming consumers. Meanwhile, quality and continuity of raw water have negative relationship.